Conférence: «Droit et féminisme - Rencontre entre deux champs» - Institut de recherches et d'études féministes; Réseau Québécois en études féministes (2018)
Avec Rachel Chagnon, membre de l'Institut de recherches et d'études féministes et professeure au Département des sciences juridiques.
Keywords: amériques; approches et analyses; discipline; discours dominant; droit; droits des femmes*; europe; féminisme décolonial; histoire du féminisme; intersectionnalité; inégalités; militance; mouvements des femmes*; rapports sociaux de sexe; régions géographiques; sciences juridiques; sociologie; système colonial; systèmes d'oppression; thématiques

Girlhood interrupted: The erasure of Black girls' childhood - Epstein, Rebecca; Blake, Jamilia J.; González, Thalia (Georgetown Law, Center on Poverty and Inequality, 2017)
This groundbreaking study by the Georgetown Law Center on Poverty and Inequality provides—for the first time— data showing that adults view Black girls as less innocent and more adult-like than their white peers, especially in the age range of 5–14. The report builds on similar results that have emerged from studies of adult perceptions of Black boys. In 2014, for example, research by Professor Phillip Goff and colleagues revealed that beginning at the age of 10, Black boys are more likely than their white peers to be misperceived as older, viewed as guilty of suspected crimes, and face police violence if accused of a crime.1 SNAPSHOT OF THE DATA Compared to white girls of the same age, survey participants perceive that • Black girls need less nurturing • Black girls need less protection • Black girls need to be supported less • Black girls need to be comforted less • Black girls are more independent • Black girls know more about adult topics • Black girls know more about sex These results are profound, with far-reaching implications. Our findings reveal a potential contributing factor to the disproportionate rates of punitive treatment in the education and juvenile justice systems for Black girls.
http://arks.princeton.edu/ark:/88435/dsp01tx31qm28z
Keywords: 2000-2029; 2010-2019; amériques; approches et analyses; discipline; droit; fem3300; filles noires*; genre; identités LGBTQIA2+; identités de genre; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique et droit; sexisme; systèmes d'oppression; thématiques; états-unis

Normal life: Administrative violence, critical trans politics, and the limits of law - Spade, Dean (Duke University Press, 2015)
Attendez—qu'est-ce qui ne va pas avec les droits ? On suppose généralement que les personnes transgenres et non conformes au genre devraient suivre les stratégies de droits civils et «d'égalité» des organisations de défense des droits des lesbiennes et des homosexuels en faisant campagne pour des réformes juridiques qui garantiraient ostensiblement la non-discrimination et une protection égale devant la loi. Cette approche suppose que la meilleure façon de lutter contre la pauvreté et la criminalisation qui affligent les populations trans est d'obtenir une reconnaissance légale et une inclusion dans les institutions de l'État. Mais cette stratégie est-elle efficace ? Dans la vie normaleDean Spade présente des critiques révélatrices du cadre d'égalité juridique pour le changement social et pointe des exemples d'activisme trans populaire transformateur qui soulève des demandes qui vont au-delà des réformes traditionnelles des droits civiques. Spade explose les hypothèses sur ce que les droits légaux peuvent faire pour les populations marginalisées et décrit les processus et les formations de résistance transformatrice qui s'attaquent aux causes profondes du mal et de la violence. Dans la nouvelle postface de cette édition révisée et augmentée, Spade note l'intégration rapide de la politique trans et constate que ses prédictions selon lesquelles l'obtention d'une reconnaissance légale ne profitera pas aux populations trans se concrétisent. Spade examine les efforts récents de l'administration Obama et des défenseurs de l'égalité des trans pour "pinkwash" la violence d'État en articulant les systèmes militaires et pénitentiaires américains comme des sites pour les réformes d'inclusion des trans. Dans le contexte de la récente visibilité accrue des personnes trans et de la politique trans, Spade continue de plaider pour le démantèlement des systèmes de violence d'État qui raccourcissent la vie des personnes trans. Aujourd'hui plus que jamais, Normal Life est un appel urgent à la justice et à la libération trans, et aux transformations radicales que cela nécessitera.
Keywords: amériques; approches et analyses; cycles supérieurs; discipline; discours dominant; droit; fem9000; identités LGBTQIA2+; identités de genre; militance; personnes trans; ressource en ligne; régions géographiques; science politique et droit; sofia; systèmes d'oppression; thématiques; violences; états-unis

Prison sexual abuse: Race, gender, and the rule of law - Buchanan, Kim (Columbia University, 2010)
In this dissertation, I argue that the exemption of prisons from the rule of law fosters abusive institutional practices that reveal the race and gender dynamics of sexual abuse in prison and in the outside world. The first article, Beyond Modesty: Privacy in Prison and the Risk of Sexual Abuse, shows that Fourth Amendment privacy offers little protection against the cross-gender searches and surveillance that expose women prisoners to sexual abuse by male guards. It proposes a reinterpretation of Fourth Amendment privacy that would recognize a constitutional right to be free from the fear, risk and reality of prison sexual abuse. The second article, Impunity: Sexual Abuse in Women's Prisons, shows that an edifice of constitutional, statutory and common-law rules confers near-complete institutional immunity against nearly all prisoner claims of custodial sexual abuse. These immunity rules parallel those of historical status regimes which excluded low-status litigants from courts on the basis of race and gender, such as civil death, slavery, segregation and the common law of marriage and rape–with similar results: low-status women of color are exposed to systematic and institutionalized sexual abuse, and are prevented from seeking protection or redress from the courts. The third article, Our Prisons, Ourselves: Race, Gender and the Rule of Law, develops these insights in men's prisons. In the absence of enforceable external rules, staff and administrators often adopt a gendered practice of institutional governance that requires prisoners to prove their manhood by fighting, and penalizes unmanly men by allowing others to rape them. These unlawful gendered practices are obscured by a false but powerful racialized narrative: most people inside and outside prison believe, inaccurately, that prison rape is mainly black-on-white. By casting sexual violence as a "complex and intractable" race relations problem for which administrators are not to blame, the racial narrative bolsters the rationale for exempting prison administration from the rule of law. Thus the perception (and reality) of unchecked prison violence supplies a reason for courts not to interfere with the unlawful institutional policies that foster it.
Accès par ProQuest
Keywords: approches et analyses; criminologie; discipline; droit; genre; intersectionnalité; mémoires/thèses; racisme; ressource en ligne; science politique et droit; sciences humaines; sexisme; sofia; systèmes d'oppression; thématiques; violences; violences sexuelles